USE OF TWO-STAGE FUEL COMBUSTION TECHNOLOGY TO MINIMIZE HAZARDOUS EMISSIONS AT KAZAKHSTAN TPP - Askarova, A.S.; Safarik, P.; Bolegenova, S.A.; Maximov, V.Yu.; Nugymanova, A.O. (Academic Scientific Journal of Computer Science, 2021)
Studies have been carried out using numerical modeling methods to determine the effect of the introduction of a two-stage combustion technology (OFA technology) of high-ash Karaganda coal on the characteristics of combustion processes: aerodynamics of flows, temperature and concentration (COх, NOх) fields throughout the entire volume of the combustion chamber of the BKZ-75 boiler at Shakhtinskaya TPP and at the outlet from it. Comparison with the basic regime of combustion of pulverized coal fuel, when there is no air supply through additional injectors (OFA = 0%). To implement the technology of two-stage combustion, various regimes of additional air supply through injectors were chosen: OFA equals 0% (basic version, conventional combustion), 5%, 10%, 15%, 18%, 20%, 25% and 30% of total air volume required for fuel combustion. A comparative analysis of the main characteristics of the heat and mass transfer process in the combustion chamber for the investigated modes is carried out. It is shown that an increase in the volume of additional air supplied through the injectors up to 18% leads to a decrease in the concentration of nitrogen oxide NO by 25% in comparison with traditional combustion. A further increase in the volume of additional air leads to a deterioration in these indicators. The results obtained will make it possible to optimize the combustion of low-grade fuel in the combustion chamber of the BKZ-75 boiler, increase the efficiency of fuel burnout, reduce harmful emissions and introduce a two-stage combustion technology at other coalfired TPPs.